Comparison Of Reduction In Blood Pressure Between Sublingual and Oral Captopril - Agustiawan, Agustiawan; Tabari, Muhammad Fadhlan La; Ilvira, Muhammad Natsir; Mastari, Ekawaty Suryani; Hardiyanti, Dwi (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Hypertensive crisis poses a high risk for long-term cardiovascular complications, and management focuses on controlled blood pressure (BP) reduction rather than immediate normalization. Objective: To compare the effectiveness of sublingual and oral captopril in reducing BP among patients with hypertensive urgency. Methods: A literature review was conducted using English-language studies published after 2012 that evaluated BP reduction outcomes of sublingual versus oral captopril. Results: Three relevant studies met the inclusion criteria, comparing both administration routes in hypertensive urgency management. All studies demonstrated that sublingual and oral captopril were similarly effective in lowering systolic and diastolic BP within the first few hours after administration. Sublingual captopril consistently produced a faster onset of action, with BP reduction observed within 15–30 minutes, whereas oral administration required 30–60 minutes to achieve comparable effects. None of the studies reported significant differences in adverse effects between the two routes. These findings suggest that while overall efficacy is comparable, the sublingual route provides more rapid BP control, which may be crucial in acute care settings. Conclusion: Both sublingual and oral captopril are effective options for hypertensive urgency, with the sublingual form offering a faster therapeutic response suitable for rapid BP reduction in emergency situations.